Peptides as 3D printable feedstocks: Design strategies and emerging applications. (January 2022) - Murphy, Robert D.; Garcia, Ronnie V.; Heise, Andreas; Hawker, Craig J.
Abstract: Peptide hydrogels have proven to be a critical building block for a range of scientific applications due to their high water capacity, tunable mechanical properties, and modular synthetic design. Particular interest stems from the biomedical realm due to their inherent biomimetic structure and biocompatibility, which has prompted their use as 3D printable matrices. In this review, we will discuss the two main strategies for preparing peptide hydrogels using solid-phase peptide synthesis (SPPS) and N -carboxyanhydride ring opening polymerization (NCA ROP) to construct the linear chains followed by gelation through either non-covalent interactions or covalent crosslinking using light or enzymes as a trigger. These synthetic approaches are summarized with a view to the applicability of hydrogel building blocks in 3D printing and representative examples illustrating the future outlook and possible research directions for the field. Graphical abstract: Image, graphical abstract